PEMBERDAYAAN MASYARAKAT MELALUI USAHA PEMBIBITAN TANAMAN MENUJU DESA JADA BAHRIN SEBAGAI SENTRA PRODUKSI BIBIT TANAMAN PERKEBUNAN DAN BUAH DI PROVINSI BANGKA BELITUNG - Ismed Inonu; Kartika Kartika; Muntoro Muntoro; Yudi Sapta Pranoto (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2014)
KKN-PPM entitled "Community Empowerment Through Plant Nursery Business Towards Jada Bahrin Village As A Center For Plantation And Fruit Seedling Production In The Province Of Bangka Belitung Islands" aims to increase students' concern and empathy for the problems of weak economic communities, especially farmers around the Universitas Bangka Belitung Campus so that there are changes in the behavior of students, farmers and farm families that are intended to be developed by the KKN PPM program. In addition, KKN PPM aims to overcome the problem of farmers' low income through community empowerment by becoming seed producers, and compiling KKN-PPM work plans that can achieve the objectives of KKN-PPM implementation as mentioned in numbers 1 and 2 above and get funding partners to support the sustainability of the business of developing Jada Bahrin Village as a seed production center. The target outcomes of the KKN-PPM program are: 1) the establishment of Jada Bahrin Village as a seedling production center for plantation and fruit crops in Bangka Belitung Islands Province, 2) at least 50 farmers and farmer families can become seedling breeders who have the knowledge and skills of vegetative plant propagation, such as grafting, grafting, grafting, and grafting, 3) the production of superior seeds of pepper, rubber, white longan, and citrus from vegetative propagation that are ready to be marketed, 4) a number of cadres have been formed for the formation of seed breeder farmer groups, which will then spearhead the formation of groups, and 5) a synergistic partnership has been established between farmers, NGOs, universities, and SOEs in order to empower the community through KKN PPM. Efforts are made through training in plant propagation techniques, construction of facilities and infrastructure, and empowerment of seedling breeder farmer groups. In the first year of KKN PPM, training on plant propagation techniques will first be conducted for a number of farmers, from the construction of mother gardens to the seed/seedling certification process. In order for the strategy to develop a plant nursery center to be achieved and sustainable, cooperation with relevant partner institutions, namely the Yayasan Bergema Emas Penghijau Lingkungan, and the Merawang Agricultural Extension Agency (BPP), will be conducted. Activities consisted of student debriefing, vegetative plant propagation training for farmers, and managerial training to strengthen farmer groups. As a result of the KKN PPM activities, 17 farmers were categorized as skilled in vegetative plant propagation, two farmer groups were formed, and a group garden for plant propagation was successfully established. These three achievements are the first step for the next stage to make Jada Bahrin Village the center of fruit and plantation seedling production in Bangka Belitung Islands Province.